Combined external beam radiotherapy with carbon ions and tumor targeting endoradiotherapy - Melzig, Claudius; Golestaneh, Azadeh Fahim; Mier, Walter; Schwager, Christian; Das, Samayita; Schlegel, Julian; Lasitschka, Felix; Kauczor, Hans-Ulrich; Debus, Jürgen; Haberkorn, Uwe; Abdollahi, Amir (OncoTarget, 2018)
External beam radiotherapy (EBRT) with carbon ions and endoradiotherapy using radiolabeled tumor targeting agents are emerging concepts in precision cancer therapy. We report on combination effects of these two promising strategies. Tumor targeting 131I-labelled anti-EGFR-antibody (Cetuximab) was used in the prototypic EGFR-expressing A431 human squamous cell carcinoma xenograft model. A 131I-labelled melanin-binding benzamide derivative was utilized targeting B16F10 melanoma in an orthotopic syngeneic C57bl6 model. Fractionated EBRT was performed using carbon ions in direct comparison with conventional photon irradiation. Tumor uptake of 131I-Cetuximab and 131I-Benzamide was enhanced by fractionated EBRT as determined by biodistribution studies. This effect was independent of radiation quality and significant for the small molecule 131I-Benzamide, i.e., >30% more uptake in irradiated vs. non-irradiated melanoma was found (p<0.05). Compared to each monotherapy, dual combination with 131I-Cetuximab and EBRT was most effective in inhibiting A431 tumor growth. A similar trend was seen for 131I-Benzamide and EBRT in B16F10 melanoma model. Addition of 131I-Benzamide endoradiotherapy to EBRT altered expression of genes related to DNA-repair, cell cycle and cell death. In contrast, immune-response related pathways such as type 1 interferon response genes (ISG15, MX1) were predominantly upregulated after combined 131I-Cetuximab and EBRT. The beneficial effects of combined 131I-Cetuximab and EBRT was further attributed to a reduced microvascular density (CD31) and decreased proliferation index (Ki-67). Fractionated EBRT could be favorably combined with endoradiotherapy. 131I-Benzamide endoradiotherapy accelerated EBRT induced cytotoxic effects. Activation of immune-response by carbon ions markedly enhanced anti-EGFR based endoradiotherapy suggesting further evaluation of this novel and promising radioimmunotherapy concept.
Gesehen am 30.03.2020